Photo-responsive polymeric micelles for the light-triggered release of curcumin targeting antimicrobial activity - Trigo-Gutierrez, Jeffersson Krishan; Calori, Italo Rodrigo; de Oliveira Bárbara, Geovana; Pavarina, Ana Claudia; Gonçalves, Renato Sonchini; Caetano, Wilker; Tedesco, Antonio Claudio; Mima, Ewerton Garcia de Oliveira (Frontiers in Microbiology, 2023)
Nanocarriers have been successfully used to solubilize, deliver, and increase the bioavailability of curcumin (CUR), but slow CUR release rates hinder its use as a topical photosensitizer in antimicrobial photodynamic therapy (aPDT). A photo-responsive polymer (PRP) was designed for the light-triggered release of CUR with an effective light activation-dependent antimicrobial response. The characterization of the PRP was compared with non-responsive micelles comprising Pluronics™ P123 and F127. According to the findings, the PRP formed photo-responsive micelles in the nanometric scale (< 100 nm) with a lower critical micelle concentration (3.74×10-4 M-1, 5.8×10-4 M-1, and 7.2×10-6 M-1 for PRP, F127, P123, respectively, at 25 °C) and higher entrapment efficiency of CUR (88.7, 77.2, and 72.3% for PRP, F127, and P123 micelles, respectively) than the pluronics evaluated. The PRP provided enhanced protection of CUR compared to P123 micelles, as demonstrated in fluorescence quenching studies. The light-triggered release of CUR from PRP occurred with UV light irradiation (at 355 nm and 25 mW cm-2) and a cumulative release of 88.34% of CUR within 1 hour compared to 80% from pluronics after 36 hours. In vitro studies showed that CUR-loaded PRP was non-toxic to mammal cell, showed photodynamic inactivation of the pathogenic microorganisms Candida albicans, Pseudomonas aeruginosa, and methicillin-resistant Staphylococcus aureus, and decreased biofilm biomass. The findings show that the CUR-loaded PRP micelle is a viable option for aPDT.